Intergenerational transmission of economic self-sufficiency: an introduction - Tosun, Jale; Pauknerová, Daniela; Kittel, Bernhard (Intergenerational transmission and economic self-sufficiency, 2021)
This chapter provides the introduction to the edited volume. It first offers a conceptualisation of the main outcome variable, economic self-sufficiency, and then provides insights from the CUPESSE survey that forms the departure point of this analysis. Afterwards, the chapter gives an overview of the volume’s structure. Then the final part summarises the main findings on the intergenerational transmission of economic self-sufficiency and concludes.